Development of Science E-module Based on Augmented Reality Using Assembler Edu on the Material of Substances and Their Changes - Salsabila, Putri; Putra, Teja Pratama; Nasir, Muhammad; Abe, Yoichiro; Linda*, Roza (Universitas Syiah Kuala, 2024)
Students' understanding of abstract concepts in the material on substances and their changes is still a challenge in science learning. This study aims to develop a valid and practical augmented reality-assisted science module using assembler edu on the material of substances and their changes. this type of research is research and development (RD) and uses the ADDIE development model. The procedures of this study include (1) the analysis stage, (2) the design stage, (3) the development stage. The data collection instruments used were a needs questionnaire, a validation questionnaire for material and media experts, a questionnaire on the practicality of teachers and students. The subjects in this study included validation test subjects consisting of 3 material experts and 3 media experts, a practicality test consisting of 3 science teachers and 30 students. The implementation of the practicality test was carried out at SMP Negeri 40 Pekanbaru in the 2024/2025 Academic Year. The results of the study show that: 1) based on the results of the validation test by material experts and media experts, the assessment scores were 0.99 and 0.97 with very valid qualifications, (2) based on the results of the practicality test by practitioners/teachers and students, the average scores were 3.75 and 3.70 with very practical qualifications. Based on the results of the validation and practicality tests, the science module assisted by augmented reality on the material of substances and their changes is declared valid and practical to be used as teaching materials in the learning process